Optimum air-demand ratio for maximum aeration efficiency in high-head gated circular conduits - Ozkan, Fahri; Tuna, M. Cihat; Baylar, Ahmet; Ozturk, Mualla (Iwa Publishing, 2014)
Oxygen is an important component of water quality and its ability to sustain life. Water aeration is the process of introducing air into a body of water to increase its oxygen saturation. Water aeration can be accomplished in a variety of ways, for instance, closed-conduit aeration. High-speed flow in a closed conduit involves air-water mixture flow. The air flow results from the subatmospheric pressure downstream of the gate. The air entrained by the high-speed flow is supplied by the air vent. The air entrained into the flow in the form of a large number of bubbles accelerates oxygen transfer and hence also increases aeration efficiency. In the present work, the optimum air-demand ratio for maximum aeration efficiency in high-head gated circular conduits was studied experimentally. Results showed that aeration efficiency increased with the air-demand ratio to a certain point and then aeration efficiency did not change with a further increase of the air-demand ratio. Thus, there was an optimum value for the air-demand ratio, depending on the Froude number, which provides maximum aeration efficiency. Furthermore, a design formula for aeration efficiency was presented relating aeration efficiency to the air-demand ratio and Froude number.
Keywords: aeration efficiency; air-demand ratio; conduit; high-head flow; oxygen transfer